Extent of Adoption of Happy Seeder Technology among the Farmers of Punjab (India) - Singh, Taranpreet; Kaur, Manmeet; Singh, Gurdeep (Indian Journal of Extension Education, 2021)
Cultivation of paddy on large area has resulted in problem paddy straw burning. Although, there are many alternatives available to the farmers but none of these is significantly adopted by them. Happy Seeder Technology (HST) was introduced to tackle the problem of paddystraw burning. The study was conducted to find the rate and extent of adoption of HST among the farmers by characterizing the extension efforts. One hundred and eighty HST adopter farmers were selected from the five agro-climatic zones Punjab. Average area under HST was about 58 per cent of the total operational land holdings of respective farmers.From awareness to adoption average forty months were taken by the farmers to complete the five stages of adoption process. Attributes of the technology viz. relative advantages, trialability, observability and compatibility had positive effect on the rate of adoption. Extension activities, easy availability of HST and large operational land holding had a positive effect on the rate of adoption of HST.